Relationship between Postoperative Pain and Sociocultural Level in Major Orthopedic Surgery - Bárbara Gouveia; Sara Fonseca; Daniel Humberto Pozza; Daniela Xará; André Sá Rodrigues (Advances in Orthopedics)
Background. Total knee arthroplasty (TKA) and total hip arthroplasty (THA) are associated with moderate to severe postoperative pain (POP). POP is theoretically predictable and may be influenced by sociocultural differences. This study aimed to identify the relationship between POP and the sociocultural level of the patient undergoing THA or TKA. Methods. Prospective study, involving informed-consenting adults conducted through consulting patient’s clinical processes, preoperative and postoperative questionnaires. Demographic and anthropometric data, type of surgery, ASA classification, sociocultural level of the patient, and POP were assessed. Results. 95 patients, all Caucasian and natural from the north of the Portugal, were included. Younger women undergoing TKA reported higher levels of POP. In females, the ASA 3 physical condition was also associated with higher mean pain intensity. Patients with preoperative chronic pain, without depression diagnosis, and unsatisfied with the current profession showed higher levels of reported POP. Retirees, with lower school degree, reported higher levels of minimal pain. Conclusions. Job satisfaction, type of surgery, body mass index, presence of chronic pain, and the absence of depression were identified as the main predictors of pain after THA or TKA.